Optimization of sodium alginate, taro starch and lactic acid based biodegradable films: Antimicrobial effect on a meat product - Hernández Nolasco, Zuemy (2024)
Sustainable biodegradable polymer films represent a key response to environmental concerns and food preservation. This study employed response surface methodology (RSM) through a Box-Behnken design, considering three factors sodium alginate (ALG) (0.75–1.5 % w/v), glycerol (G) (0.5–1 % w/v), and lactic acid (LA) (1-3 % v/ v), to obtain an optimized biodegradable film (OBF) of taro starch (TAS). The resulting optimal composition was 1.04 % w/v ALG, 0.75 % w/v G, and 1.25 % v/v LA, with a thickness of 0.14 mm and a WVP of 1.05 g⋅mm/ kPa⋅h⋅m2 . The LA in OBF increased elongation by 23.24 % and demonstrated inhibition areas exceeding 5.00 cm2 against E. coli and L. monocytogenes. FTIR and SEM analysis confirmed the covalent cross-linking between TAS-LA and revealed compatibility among matrix materials. OBF was employed as an active packaging system (T3) in a Spanish chorizo-type meat product to evaluate its physicochemical and microbiological properties. The most significant changes (humidity, weight loss, aw, pH, acidity, hardness) occurred within the first nine days. T3 inhibited the growth of coliforms and reduced populations of mesophiles and lactic acid bacteria by ~1 log cycle. OBF guarantees meat product quality and microbial properties while supporting sustainable practices through environmentally respectful biodegradation.